Сутність договору про поділ спадщини та його місце в системі цивільно-правових договорів - Кухарєв, О. Є.; Kukharev, O. Y.; ORCID: http://orcid.org/0000-0003-2086-9179 (Вісник Харківського національного університету внутрішніх справ. – 2022. – № 4 (99). – С. 81-92, 2022)
Розкрито сутність договору про поділ спадщини через сукупність його визначальних ознак: 1) укладається після спливу строку для прийняття спадщини, але до видачі спадкоємцям свідоцтва про право на спадщину; 2) сторонами виступають спадкоємці, які прийняли спадщину у спосіб та строки, визначені цивільним законодавством; 3) має значно менше, допоміжне значення порівняно з цивільно-правовим договором, оскільки породжує правові наслідки в сукупності з іншими юридичними фактами; 4) за наявності насцитуруса договір може бути укладений лише після народження дитини; 5) поділ спадщини здійснюється з урахуванням переважного права окремих спадкоємців на виділ їм спадкового майна в натурі. Обґрунтовано, що договір про поділ спадщини належить до групи договорів у сфері спадкового права, а його предметом виступає спадщина як об’єкт цивільних прав. Правовстановлюючим документом на спадкове майно є не договір про поділ спадщини, а свідоцтво про право на спадщину, що видається нотаріусом на виконання цього договору. Наголошено на можливості укладення договору про поділ спадщини незалежно від виду спадкування – за заповітом або законом.

The article reveals the essence of the contract for division of inheritance through a set of its defining features: 1) it is concluded after the expiry of the period for acceptance of the inheritance, but before the heirs receive a certificate of inheritance; 2) the parties are the heirs who have accepted the inheritance in the manner and within the time limits specified by civil law; 3) it has a much smaller, auxiliary value compared to the role of a civil law contract, as it generates legal consequences in conjunction with other legal facts; 4) in the presence of a nasciturus, the contract may be concluded only after the birth of a child; 5) the division of the inheritance is carried out taking into account the preemptive right of individual heirs to receive inheritance property in kind. An inheritance division agreement belongs to the group of agreements in the field of inheritance law, and its subject matter is inheritance as an object of civil rights. The legal document for inheritance is not the agreement on the division of inheritance, but the certificate of the right to inheritance, issued by a notary for the execution of this agreement. Based on the legislative construction of Art. 1278 of the Civil Code of Ukraine it has been stated that the method of dividing the inheritance is the allocation of a share in kind, as a result of which the ideal share in the inheritance turns into a real one. The agreement on the division of the inheritance can be concluded by the heirs regardless of the type of inheritance, in particular, by will or by law. The contract under study may contain a condition for changing the size of the inheritance shares. However, the heirs cannot change the size of their shares in the inheritance if the testator personally set them in the will. In the presence of a will, priority should be given to the will of the testator, which cannot be changed by the heirs. Otherwise, the principle of freedom of will be violated. It is no coincidence that Art. 1267 of the Civil Code of Ukraine, which determines the change in the size of shares in the inheritance, is structurally placed in Chapter 86 “Inheritance by law”.

Раскрыта сущность договора о разделе наследства через совокупность его определяющих признаков: 1) заключается после истечения срока для принятия наследства, но до выдачи наследникам свидетельства о праве на наследство; 2) сторонами выступают наследники, принявшие наследство способом и в сроки, определенные гражданским законодательством; 3) имеет значительно меньшее, вспомогательное значение по сравнению с гражданско-правовым договором, поскольку порождает правовые последствия в совокупности с другими юридическими фактами; 4) при наличии насцитуруса договор может быть заключен только после рождения ребенка; 5) разделение наследства осуществляется с учетом преимущественного права отдельных наследников на выделение им наследственного имущества в натуре. Обосновано, что договор о разделе наследства относится к группе договоров в области наследственного права, а его предметом выступает наследство как объект гражданских прав. Правоустанавливающим документом на наследственное имущество является не договор о разделе наследства, а свидетельство о праве на наследство, которое выдается нотариусом во исполнение настоящего договора. Отмечена возможность заключения договора о разделе наследства независимо от вида наследования – по завещанию или закону.
The essence of the inheritance division agreement and its place in the system of civil law contracts
Кухарєв, О. Є. Сутність договору про поділ спадщини та його місце в системі цивільно-правових договорів / Олександр Євгенович Кухарєв // Вісник Харківського національного університету внутрішніх справ. – 2022. – № 4 (99). – С. 81-92. - DOI: https://doi.org/10.32631/v.2022.4.07.
Кухарєв, О. Є. (2022) «Сутність договору про поділ спадщини та його місце в системі цивільно-правових договорів», Вісник Харківського національного університету внутрішніх справ, 99(4), с. 81-92. doi: 10.32631/v.2022.4.07.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Спадкове право. Inheritance law. Наследственное право; спадкування; inheritance; наследование; спадкоємець; heir; наследник; договір про поділ спадщини; agreement on division of inheritance; договор о разделе наследства; спадкове майно; inherited property; наследственное имущество; ідеальна спадкова частка; perfect inheritance share; идеальная наследственная доля; реальна спадкова частка; real inheritance share; реальная наследственная часть